Improvement in DTC-SVM of AC drives using a new robust adaptive control algorithm, ISSN 1598-6466 - Sebti Belkacem; Naceri Farid (International journal of control automation and system, IJCAS, 2011)
In this paper a new robust adaptive speed controller algorithm for AC motor drives is presented. The main feature of this algorithm is that minimum synthesis is required to implement the strategy. MCS algorithm is a significant development of MRAC. The stability of the proposed system is achieved through Popov’s Hyperstability criteria. The new algorithm appeared to be robust in the face of totally unknown plant dynamics, external disturbances and parameter variations with the plant. Finally, a new approach has been successfully implemented on DTC-SVM. Extensive simulation results are presented to validate the proposed technique. The system is tested at different speeds and a very satisfactory performance has been achieved.